Model pembelajaran project based learning berbasis potensi lokal pada mata pelajaran prakarya dan kewirausahaan (SMA/SMK di Malang) - Laily Fitria Wati (Jurnal Teori dan Praksis Pembelajaran IPS, 2018)
Project Based Learning model based on local potential is a project-based learning model, the resulting project is a business proposal, processed food products and packaging labels and small business practices in the School. Food processing products produced are foods or beverages that utilize the local potential of agricultural products in Malang. Potential of Malang area include agricultural products spread in Malang area that is apple, strawberry, orange juice, bark, banana, sweet potato. The last project is a small business practice formed by several students who work with school cooperatives. This small business is a temporary business that is practiced in schools with business actors are the students who are formed in several groups, the activity is to sell the results of the food processing business project in the school cooperative. Processed food products can be produced food, snacks or drinks. The learning model is applied to the subjects of entrepreneurship and is the subject of knowledge transfer that is taught in all majors at the senior high school or vocational high school level, where the material contained in the subjects consists of four aspects: craft, engineering, cultivation and processing. Each school is required to take one material aspect. Project Based Learning model is applied to food processing aspect on the subjects of workshop and entrepreneurship.DOI: 10.17977/um022v3i12018p039